Tangguh Hadapi Covid-19 dengan Budidaya Tanaman Obat Keluarga di Desa Margomulyo, Seyegan, Sleman - Wiwit Probowati; Fuad Gandhi Torizal; Sunartiyah Sunartiyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
During the Covid-19 outbreak, it is essential to maintain faith and a happy soul; it is also necessary to maintain our health immunity. The body's immunity can be supported by consuming healthy food and a balanced diet. Consumption of additional supplements from chemical medicine cause side effects if consumed overdoses. By utilizing the land yard for the cultivation of herbal plants, it can be used as an alternative solution to reduce the consumption of chemical drugs, in line with the problems faced by the program partner nursery, which has an extensive collection of medicinal plants but does not yet know the efficacy of each type of plant. The community service program during the pandemic was carried out through limited counseling to 30 health cadres of Margomulyo village. The method used in this activity is public education through lectures, questions, and discussions. Participants were also given a pocketbook "List of Herbal Plants and their benefits and also given plant seeds. Participants' level of knowledge was measured using a questionnaire given before and after the lecture. From the results, it can be seen that there is an increase in the understanding of the participant's post-test scores compared to pre-test scores. Participants' increased knowledge about family medicinal plants was expected to share the knowledge with the broader community and apply the cultivation of herbal plants inland around the house.